Design and Fabrication of Biodegradable Microneedle Using 3D Rapid Prototyping Printer. (November 2019) - Mansor, Nur Hazwani Azyan; Markom, Marni Azira; Tan, Erdy Sulino Mohd Muslim; Adom, Abdul Hamid
Abstract: Microneedle is known as transdermal drug delivery (TDD) devices that uses to deliver biological fluid into veins and needle that use to tear skin to collect blood sample. It involves with various parameters and designs. This device gain attention as its benefit can eliminate pain and more convenient compared to intravenous injection due to its micron size. Typically, microneedle is fabricated using MEMS technology. However, this technology requires few processes such as deposition, etching and moulding, as well as consume much times. This paper presents a work of design and fabrication of solid microneedle using 3D rapid prototype printing. A few types of microneedles are designed and they are analysed in terms of stress and force characteristics. Also, it will study the ability of a few materials to withstand stress while force exerted on it. The selected materials are polyvinyl alcohol (PVA), polylactic acid (PLA), polyester resin and acrylonitrile butadiene styrene (ABS). The results show that PVA has the highest ability to withstand force compared other materials. As conclusion, the design and fabrication of microneedle using 3D rapid prototyping printer is succeed using PVA material and real post-analysis can be conducted to test the capability for medical practice.